Surgical Injury and Ischemia Prime the Adipose Stromal Vascular Fraction and Increase Angiogenic Capacity in a Mouse Limb Ischemia Model - Satoko Kishimoto; Ken-ichi Inoue; Ryoichi Sohma; Shigeru Toyoda; Masashi Sakuma; Teruo Inoue; Ken-ichiro Yoshida (Hindawi Limited, 2020)
The adipose-derived stromal vascular fraction (SVF) is an effective source for autologous cell transplantation. However, the quality and quantity of SVFs vary depending on the patient's age, complications, and other factors. In this study, we developed a method to reproducibly increase the cell number and improve the quality of adipose-derived SVFs by surgical procedures, which we term "wound repair priming." Subcutaneous fat from the inguinal region of BALB/c mice was surgically processed (primed) by mincing adipose parenchyma (injury) and ligating the subcutaneous fat-feeding artery (ischemia). SVFs were isolated on day 0, 1, 3, 5, or 7 after the priming procedures. Gene expression levels of the primed SVFs were measured via microarray and pathway analyses which were performed for differentially expressed genes. Changes in cellular compositions of primed SVFs were analyzed by flow cytometry. SVFs were transplanted into syngeneic ischemic hindlimbs to measure their angiogenic and regeneration potential. Hindlimb blood flow was measured using a laser Doppler blood perfusion imager, and capillary density was quantified by CD31 staining of ischemic tissues. Stabilization of HIF-1 alpha and VEGF-A synthesis in the SVFs were measured by fluorescent immunostaining and Western blotting, respectively. As a result, the number of SVFs per fat weight was increased significantly on day 7 after priming. Among the differentially expressed genes were innate immunity-related signals on both days 1 and 3 after priming. In primed SVFs, the CD45-positive blood mononuclear cell fraction decreased, and the CD31-CD45-double negative mesenchymal cell fraction increased on day 7. The F4/80-positive macrophage fraction was increased on days 1 and 7 after priming. There was a serial decrease in the mesenchymal-gated CD34-positive adipose progenitor fraction and mesenchymal-gated CD140A-positive/CD9-positive preadipocyte fraction on days 1 and 3. Transplantation of primed SVFs resulted in increased capillary density and augmented blood flow, improving regeneration of the ischemic limbs. HIF-1 alpha was stabilized in the primed cutaneous fat in situ, and VEGF-A synthesis of the primed SVFs was on a peak on 5 days after priming. Wound repair priming thus resulted in SVFs with increased number and augmented angiogenic potential.